2014
DOI: 10.1186/1471-2334-14-399
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of new smear positive pulmonary tuberculosis patients in Penang, Malaysia

Abstract: BackgroundAccording to the World Health Organization’s recent report, in Malaysia, tuberculosis (TB) treatment success rate for new smear positive pulmonary tuberculosis (PTB) patients is still below the global success target of 85%. In this study, we evaluated TB treatment outcome among new smear positive PTB patients, and identified the predictors of unsuccessful treatment outcome and longer duration of treatment (i.e., > 6 months).MethodsThe population in this study consisted of all new smear positive PTB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 19 publications
10
58
2
1
Order By: Relevance
“…Probably this may be because all the patients in our study came from the same country (tribe). Studies done in Swit-zerland and Malaysia showed significant difference between indigenous cases and that of the foreigners [12] [15].…”
Section: Discussionmentioning
confidence: 99%
“…Probably this may be because all the patients in our study came from the same country (tribe). Studies done in Swit-zerland and Malaysia showed significant difference between indigenous cases and that of the foreigners [12] [15].…”
Section: Discussionmentioning
confidence: 99%
“…The medical records and TB notification forms of the patients were reviewed to obtain sociodemographic, clinical and treatment-related data. 4,5,8,9 The normal benchmarks for the duration of the IP and CP of treatment are two and four months, respectively. 2 A patient in whom the clinicians decided to extend the IP of treatment by !…”
Section: Study Settingmentioning
confidence: 99%
“…A detailed description of the study setting is available in the authors' other published papers which differ in terms of their objectives and outcomes. 7,8 Study design and data collection This descriptive, non-experimental, follow-up cohort study involved all new smear-positive PTB patients who received WHO-recommended standard TB treatment 2 at the study site between March 2010 and February 2011. Each patient was followed-up until his/her final treatment outcome was available (i.e.…”
Section: Study Settingmentioning
confidence: 99%
“…In this study, we investigated the sputum smear conversion time in TB and HIV co-infected patients with confirmed mutations on rifampicin (RIF) and isoniazid (INH) conferring genes. Calculation of sputum conversion time is an important measure for determining the progress of treatment (14) . Previous studies have shown that the H526Y and the S531L mutations are associated with higher minimum inhibitory concentrations for RIF and therefore poor drug response (3) .…”
Section: Discussionmentioning
confidence: 99%